Minat Pendidik Dalam Pemanfaatan Media Pembelajaran - Hafaztha Dzikri; Agus Salim Salim; Ramadhan Nur Ilham; Rizki Audiva Aisyah (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Abstract: In the learning process, the media as a tool has a very big role in improving the quality of learning in a place. The research title is Lack of Teacher or Educator's Interest in Using Learning Media. The purpose of this study is to examine how far an interactive dialogue between a teacher and students is done dynamically and efficiently in early childhood education. The research method using  is descriptive method. Data collection techniques by looking at the conditions around, reading info and reading books connecting to  learning media. The research subject is an early childhood teacher. The results of the research showed: 1) educators easily give lessons with a variety of learning methods that are assisted by a learning medium including digital media, 2) media is a need that cannot be separated in all aspects, 3) not all teachers are able to use assistive devices learning media, 4) the instructor has difficulty when delivering his learning material, because he cannot display the subject matter. Keywords     : Teacher and Learning media